2022
DOI: 10.1044/2021_ajslp-21-00139
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Caregiver Satisfaction With a Telediagnostic Assessment of Autism Spectrum Disorder

Abstract: Purpose: In light of the COVID-19 pandemic, it is critical to understand the feasibility and acceptability of the use of telediagnostic assessments in clinical settings. This study aimed to characterize caregiver satisfaction with a telediagnostic assessment of autism spectrum disorder (ASD). Method: Twelve families completed a telediagnostic assessment of ASD through Illinois' Early Intervention program including a caregiver interview, administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Analysis of clinician-reported data both within (Wagner et al, 2020 ) and external to our institution (Wagner et al, 2022 ) indicated that clinicians were able to make definitive diagnostic decisions via tele-assessment for a majority of children with a high degree of diagnostic certainty. Additional external studies of tele-assessment using the TAP highlighted caregiver satisfaction with tele-assessment procedures, including logistical convenience, positive interactions with clinicians, and satisfaction with diagnostic feedback and recommendations (Jones, 2022 ; Stavropoulos et al, 2022 ). However, the rapid roll-out of the TAP in response to the urgent need for telemedicine tools preceded controlled investigation of the TAP in comparison to traditional, in-person assessment.…”
mentioning
confidence: 99%
“…Analysis of clinician-reported data both within (Wagner et al, 2020 ) and external to our institution (Wagner et al, 2022 ) indicated that clinicians were able to make definitive diagnostic decisions via tele-assessment for a majority of children with a high degree of diagnostic certainty. Additional external studies of tele-assessment using the TAP highlighted caregiver satisfaction with tele-assessment procedures, including logistical convenience, positive interactions with clinicians, and satisfaction with diagnostic feedback and recommendations (Jones, 2022 ; Stavropoulos et al, 2022 ). However, the rapid roll-out of the TAP in response to the urgent need for telemedicine tools preceded controlled investigation of the TAP in comparison to traditional, in-person assessment.…”
mentioning
confidence: 99%